Associations between heavy traffic near residence and childhood health outcomes as modified by bedroom floor level and bedroom ventilation. (March 2017) - Chang, Jing; Liu, Wei; Hu, Yu; Zou, Zhijun; Shen, Li; Wang, Xueying; Cai, Jiao; Sun, Chanjuan; Huang, Chen
Abstract: During 2011–2012, we conducted a cross-sectional study and collected 13, 335 parent-reported questionnaires for 4-6 year-old children in Shanghai, China. In this study, we investigated associations of LC-HTRH (Living Close to High Traffic Roads or Highways within 200 m of the residence) with childhood health outcomes. In the multiple logistic regression analyses, LC-HTRH was significantly associated with lifetime-ever doctor-diagnosed asthma (adjusted OR, 95% CI: 1.40, 1.16–1.70). LC-HTRH and bedroom floor level had significant interaction effects on lifetime-ever asthma attack and eczema and past-year eczema. In the subanalyses, LC-HTRH was significantly associated with lifetime-ever asthma (1.52, 1.11–2.09) and asthma attack (1.69, 1.11–2.56) among children who lived on the 4th–6th floors. LC-HTRH was significantly associated with the increased odds of lifetime-ever asthma and past-year rhinitis in summer, autumn, and winter among children whose bedroom windows were opened often. Furthermore, more significant associations between LC-HTRH and the studied outcomes were found among children who both lived in low floor levels and came from families who often opened bedroom windows during night than others. Except for lifetime-ever asthma, no significant associations were found between LC-HTRH and all studied outcomes among children from families who did not often open bedroom windows during night in the different floor levels. This study indicates that LC-HTRH might be associated with part of childhood health outcomes. When ambient air is polluted, increasing bedroom ventilation might lead household air quality at low-medium levels worse, and thus increase odds of some childhood allergic and respiratory problems. Highlights: We studied effects of bedroom floor level and ventilation on associations of heavy traffic with children's health. Heavy traffic was associated with increased odds of asthma and asthma attack in children lived on the 4th–6th floors. Heavy traffic near home had interaction effects with family ventilation habits on asthma and rhinitis. Increasing bedroom ventilation could increase odds of children's respiratory problems when ambient air is polluted.